Humility, Religion, and Spirituality: Introduction to the Special Issue - Hook, Joshua N. (Journal of psychology and theology, 2014)
This issue of the Journal of Psychology and Theology focuses on the intersection between humility, religion, and spirituality. In this introduction to the special issue, we first define humility, religion, and spirituality. Then, we present some initial theory and research that motivated our desire to organize this special issue. Namely, humility is a virtue that is often taught and valued by world religions. However, it may be difficult to hold religious/spiritual convictions with humility, and history is replete with examples in which religion has fueled the fires of conflict and division between individuals and groups. After setting up this tension between humility and religion/spirituality, we summarize the subsequent articles in this issue, which explore this important and timely topic.